Monumenter til hverdags - Selberg, Torunn (Tidsskrift for kulturforskning, 2007)
This article concerns everyday narratives about monuments in local communities. The material used is collected through Norsk Etnologisk Gransking. The narratives demonstrate that a monument in most cases is connected to war memorials, especially those related to the 2nd World War. The narratives also show great local variation connected to the monuments that are related to the national history, stories about the 2nd World War present local diversity, sometimes in opposition to the national one. We also learn that a monument, although representing a memory from the past, must talk to the present in order to be remembered, and that a monument consists of the stone, the narratives and rituals connected to it.